A corner reflector of graphene Dirac fermions as a phonon-scattering sensor - H. Graef (Nature Portfolio, 2019)
Dirac fermion optics leverages p-n junctions and Klein tunnelling barriers present in materials to implement complex optical functions and devices, including reflectors, collimators, and Dirac fermion microscopes. Here, the authors fabricate Dirac fermion corner reflectors using bottom-gate-defined barriers in hBN-encapsulated graphene, and demonstrate high-frequency operation.